Mindfulness influence on psychological wellbeing: in search of cultural adaptations - Paz, Reut; Davidovitch, Nitza (Frontiers in Psychology, 2025)
IntroductionIn the last decade, mindfulness-based programs have been assimilated among educational staff to cultivate socio-emotional skills and mental resilience. Most mindfulness programs use generic international models, omitting explicit acknowledgement of cultural and ethnic differences. Recent research highlights the importance of considering participants’ identities and diverse cultural and religious needs. The first aim of the current study is to explore whether mindfulness affects psychological well-being among Orthodox Jewish teachers. Additionally, the study examined the relationship between mindfulness as a personality trait and psychological well-being and resilience among Orthodox Jewish teachers. The second aim is to examine whether there is a tension in practicing mindfulness among participants who are Orthodox educators, and whether there is a need for cultural adaptations for religious populations to increase the effectiveness of the program.MethodsThe participants in this pioneer study were Orthodox teachers and principals from state religious schools who participated in the mindfulness program. The questionnaires were distributed among Orthodox teachers to characterize the group on several measures related to psychological well-being and resilience, as well as on measures of religiosity, to clarify whether there is an association between deep-rooted religious foundations and perceived mental resilience.ResultsThe research findings indicate that trait mindfulness and mindfulness training are related to increased psychological well-being and resilience. Trait mindfulness was significantly negatively associated with perceived stress. The study also showed that ultra-Orthodox teachers reported a higher sense of stress than did national religious teachers.DiscussionIt is evident from the current study that mindfulness qualities may support resilience and psychological well-being among Orthodox educators, whereupon it is important to nurture these qualities among them via mindfulness-based professional development. Moreover, it is evident from the study that to increase the efficacy of these programs, it is necessary to be aware of the participants’ ethnic, religious, and cultural features.